The Act of Multicultural Politeness Understanding Among Ethnicities in Manokwari: Maintaining the Spirit of Indonesian Unity (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
As one of the largest multicultural countries, the differences in race, ethnicity, religion, and language are all represented in Indonesia. The international community may find Indonesia's good potential and distinctive variety to be particularly alluring. However, we should consider that variety also opens up a number of negative consequences, as equal as its positif opportunities. It has repeatedly been reported that Indonesia was hit by diversity conflicts. Take an example from eastern Indonesia, specifically in Manokwari, West Papua. There was a conflict between ethnicities once in 2019, where misunderstanding is one of the conflict causes. The conflict was raised from the case where a person’s acts were misunderstood as impoliteness to another ethnic. As the research Purpose, this research will be conducted to unveil how each ethnicity applied the act of politeness, and what factors prevent multicultural politeness understanding among Papuans, Javanese, Makassarians, and Madurians who live together in Manokwari. Rooting the theory toward Brown and Levinsons’ politeness, this research will be conducted using the ethnography method, where there are 9 villages in total. The result shows there are varieties of politeness used among ethnicities. However, the research provides valuable insights into the nuances of multicultural politeness understanding among the Papuan, Javanese, Makassarian, and Madurian ethnicities in Manokwari. There are several aspects that play a role in preventing multicultural politeness understanding such as cultural differences in politeness, language barrier, historical and social factors.